The Finnish developmental state and its growth regime - Markus Jäntti; Juhana Vartiainen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper reviews Finland's growth strategy in the postwar decades. Finland was able to initiate an impressive mobilization of resources during this period, reflected mostly in a high rate of capital accumulation for manufacturing industries. This was achieved by an unorthodox combination of dirigiste means and a basic commitment to upholding the market economy. The state acted as a net saver, and credit was rationed to productive investment outlays. This policy package may have been boosted by the country's precarious international position during the cold war, so that an economic failure would have been very risky indeed. We argue also that incomes policies and welfare reforms were important in sustaining the necessary political compromise that underpinned the Finnish development state.
Keywords: O43; E64; O15; J5; 330; economic growth; incomes policy; income distribution; labour unions; structural transformation; social contacts; developmental state; Wachstumspolitik; Einkommenspolitik; Einkommensverteilung; Gewerkschaft; Wirtschaftliche Anpassung; Finnland